Tracking the changing body with care: a qualitative study on menstrual cycle tracking among adolescent girls in Bali, Indonesia - Heather Suttor; Kadek Putri Yamayanti; Ni Luh Eka Purni Astiti; Tungga Dewi; Ansariadi Ansariadi; Julie Hennegan; Richard D. Chenhall (International Journal of Adolescence and Youth)
Menstrual cycle tracking is increasingly integrated into menstrual health education and is frequently supported by mobile applications. While menstrual cycle tracking can help adolescents understand their bodies and cycles, research into their everyday tracking practices remains limited. We conducted a participatory and ethnographic study with 24 adolescent girls and six adults, including teachers, in Bali, Indonesia. Drawing on data from group discussions, interviews, and participant observation, we describe how participants engaged and experimented with menstrual cycle tracking. Guided by a ‘logic of care’, we explore how participants tracked their menstrual cycles in sporadic, relational and embodied ways and how these practices diverged from the systematic and individualised approach to tracking imagined through apps. We found participants adapted tracking practices according to their changing bodies, local contexts, and the perceived usefulness of tools and technologies. We propose that care provides menstrual health researchers and practitioners a valuable lens to explore adolescents’ emerging menstrual practices, while enriching discussions on menstrual tracking education and the use of health-supporting technologies among younger populations.